Pattern visual evoked potential (PVEP) evaluation in hypothyroidism - Nazliel, Bijen; Akbay, E.; Irkeç, C.; Yetkin, I.; Ersoy, R.; Törüner, F. (Journal of endocrinological investigation, 2002)
Dysfunction of the central nervous system (CNS) is an important consequence of thyroid hormone deficiency. Evoked potentials like visual evoked potentials (VEP) provide a reliable and objective measure of function in related sensory system and tracts. In this study pattern-shift VEP (PVEP) recordings were performed on 48 newly diagnosed hypothyroid patients. Twenty-four had sub-clinical and 24 had overt hypothyroidism. None of the patients had clinical symptoms or signs referable to CNS dysfunction. Their mean age was 44+/-12 yr. The response to pattern stimulation on the normal control subjects was a triphasic response with a prominent positive wave (P100) with a peak latency of 84-105 (mean: 96+/-4) milliseconds (ms). In patients with hypothyroidism mean P100 latency was (mean: 97+/-6) ms and the difference between the 2 groups was not statistically significant. (p>0.05) Delays above the average latency +/-2.5 SD of the mean of the control subjects was defined as a criteria for an abnormality. According to defined criteria 6 (12.5%) patients demonstrated abnormal PVEP at least on one tested side. Previous studies conducted on small patient populations stated there is high percentage of VEP abnormalities in hypothyroid patients. However, this fact was not confirmed by our study. We believe abnormalities of PVEP will be more prominent in untreated patients in the advanced stage of the disease, or in patients who have a neurological involvement; such as apathy, impaired memory or cerebellar dysfunction. Consecutive studies, in a more clearly defined and selected patient population, are needed to confirm and settle this issue.